The Influence of Project-Based Learning Assisted by Artificial Intelligence-Based Mind Mapping on Digital Literacy Competence of Biology Education Students - Tendrita, Miswandi; Hidayati, Ully (KULIDAWA, 2024)
This study aims to evaluate the impact of Project-Based Learning (PjBL) assisted by Artificial Intelligence (AI)-based mind mapping on the digital literacy competency of biology education students at Sembilanbelas November University (USN) Kolaka. The sample used in this study was students of the 2021 batch of USN Kolaka. This study used a one-group pretest-posttest design. The research instrument was a digital literacy questionnaire compiled based on information, communication, content-creation, social-emotional, and problem-solving indicators. Data analysis was descriptive (average) and inferential (paired sample t-test). The findings indicated that biology education students' average posttest value for digital literacy competency was 77.96 > the average pretest value of 61.06. The significance value of digital literacy competency was 0.000 < the significance value of α of 0.05, so it can be inferred that the implementation of PjBL assisted by AI-based mind mapping can facilitate more innovative and interactive learning and encourage the development of students' digital skills.